The contribution of a novel PHEX gene mutation to X-linked hypophosphatemic rickets: a case report and an analysis of the gene mutation dosage effect in a rat model - Chen, Xiaoming; Cai, Cijing; Lun, Shaocong; Ye, Qiuli; Pan, Weiyuan; Chen, Yushi; Wu, Yuexuan; Feng, Taoshan; Su, Faming; Ma, Choudi; Luo, Jiaxin; Liu, Meilian; et al. (Frontiers in Endocrinology, 2023)
A Chinese family was identified to have two patients with rickets, an adult female and a male child (proband), both exhibiting signs related to X-linked hypophosphatemic rickets (XLH). Gene sequencing analysis revealed a deletion of adenine at position 1985 (c.1985delA) in the PHEX-encoding gene. To investigate the relationship between this mutation and the pathogenicity of XLH, as well as analyze the effects of different dosages of PHEX gene mutations on clinical phenotypes, we developed a rat model carrying the PHEX deletion mutation. The CRISPR/Cas9 gene editing technology was employed to construct the rat model with the PHEX gene mutation (c.1985delA). Through reproductive procedures, five genotypes of rats were obtained: female wild type (X/X), female heterozygous (-/X), female homozygous wild type (-/-), male wild type (X/Y), and male hemizygous (-/Y). The rats with different genotypes underwent analysis of growth, serum biochemical parameters, and bone microstructure. The results demonstrated the successful generation of a stable rat model inheriting the PHEX gene mutation. Compared to the wild-type rats, the mutant rats displayed delayed growth, shorter femurs, and significantly reduced bone mass. Among the female rats, the homozygous individuals exhibited the smallest body size, decreased bone mass, shortest femur length, and severe deformities. Moreover, the mutant rats showed significantly lower blood phosphorus concentration, elevated levels of FGF23 and alkaline phosphatase, and increased expression of phosphorus regulators. In conclusion, the XLH rat model with the PHEX gene mutation dosage demonstrated its impact on growth and development, serum biochemical parameters, and femoral morphology.